Fertility knowledge and views on egg freezing and family planning among surgical specialty traineesAJOG Global Reports at a Glance - Karine Matevossian, DO; Anne Rivelli, MA, MPH; Meike L. Uhler, MD (Elsevier, 2022)
BACKGROUND: There are limited studies focusing on resident and fellow attitudes on family planning and egg freezing. Surgical training programs are often longer and more time consuming than other fields. It is important to understand how this training affects family planning decisions. OBJECTIVE: This study aimed to describe fertility knowledge and viewpoints on family planning among US residents or fellows. STUDY DESIGN: The Advocate Aurora Health Institutional Review Board approved this study on October 8, 2019 (IRB# AHC-7213-S5500413). A 32-question survey was emailed to trainees across US programs in a variety of specialties (obstetrics/gynecology; ophthalmology; otolaryngology; urology; and neurology, plastic, general, thoracic and orthopedic surgery) to assess fertility knowledge. Pearson chi square tests were conducted to investigate differences in fertility knowledge by groups of interest (trainee specialty, gender, trainee program type). Demographics and viewpoints on family planning and egg freezing are described. All analyses were performed using SAS, version 9.4. RESULTS: A total of 447 surveys were collected from October 2019 to January 2020. Participants included 309 residents, 94 fellows, and 44 with unknown status across the 9 specialties. Participants were mostly female (73%), aged 26 to 30 years (48%), White (69%), married (59%), and heterosexual (95%), with no children (72%). When asked at what age a woman's fertility slightly decreases, obstetrics/gynecology trainees had 39% less likelihood of answering correctly compared with non-obstetrics/gynecology respondents (P=.0207). Female respondents had 18% less likelihood of answering correctly relative to male respondents, and trainees in academic programs were 20% to 60% more likely to answer correctly relative to those in community programs, but these findings were not statistically significant. Interestingly, female respondents had 2.89 times increased odds of having 0 children (P<.0001), 0.42 times increased odds (ie, 58% decreased odds) of being married (P=.0003), and 1.33 times increased odds of postponing childbearing (P=.2438). CONCLUSION: This study found that despite their sex or focused training in reproductive endocrinology and infertility, female respondents and obstetrics/gynecology trainees were not more well-versed in basic female fertility knowledge than their counterparts. Furthermore, female respondents were less likely to have children or be married, and more likely to report postponing childbearing, highlighting differences in family planning by sex. Fertility-focused educational interventions for obstetrics/gynecology trainees are necessary. More research into barriers to family planning, particularly by sex, are also merited.